VD_FINDINFO Arrêt / 2012 / 613 vom 25. Mai 2012 - VD Tribunal cantonal (2012)
BIENS DE L'ENFANT, ADMINISTRATIONACTIVITÉ, MESURE DE PROTECTION, AUTORITÉ PARENTALE | 318 al. 3 CC, 324 CC, 399a CPC, 489 CPC